FAKTOR-FAKTOR YANG MEMENGARUHI MINAT GENERASI MILENIAL MEMILIH BERINVESTASI PADA PLATFORM DIGITAL - Yolanda Liviana; Munawaroh (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study’s purpose was to analyze the influence of financial literacy, personal interests, and digital investment application services on the Millennial's investment interest in the Bibit Application, a Mutual Fund Investment platform for beginners. Using 100 samples and multiple linear regression analysis shows that partially, both personal interests and digital investment sevices have significant impact on the Millennial's interest in investing on this digital platform. Furthermore, all variables simultaneously also have a significant effect.